Augmented Reality in the Construction Industry: Use-Cases, Benefits, Obstacles, and Future Trends - Nassereddine, Hala; Hanna, Awad S.; Veeramani, Dharmaraj; Lotfallah, Wafik (Frontiers in Built Environment, 2022)
Information is the lifeblood of modern construction. Advances in Information and Communication Technology have been and are continuing to progress at rapid rates. Construction companies that are successfully able to adopt and integrate new technologies will gain a competitive edge. One emerging technology that has great potential to transform the construction industry is Augmented Reality (AR). While AR has been of interest to researchers for some time, no single research effort has yet comprehensively investigated the opportunities, benefits, challenges, and future paths toward implementing AR in modern construction. The main objective of this research is to investigate the potential of AR throughout the lifecycle of a construction project from the perspective of the construction industry. Responses from 93 industry practitioners were collected to investigate use-cases of AR throughout the project lifecycle, highlight potential benefits, and identify obstacles to entry which have slowed the implementation of AR thus far. Cluster analysis was employed to determine AR use-cases with the highest usage potential and identify the highest perceived benefits and obstacles of AR. Finally, the future of AR in construction is forecast through a series of statements that describe potential trends of AR in the construction industry. This study contributes to the existing body of knowledge by exploring the potential of AR as perceived by construction practitioners.